1996
DOI: 10.1055/s-2007-999049
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Degradation in the Synovial Fluid of Rheumatoid Arthritis Patients: A Model for Extravascular Fibrinolysis

Abstract: The patterns of degradation and the influence of factor XIII polymerization on fibrin stability were examined in vitro following incubation with leukocyte elastase. In vivo experiments, various factor XIII-polymerized fibrin clots were implanted subcutaneously in mice to evaluate the stability of clots in the extravascular space. Both in vitro and in vivo lysis proceeded faster with nonpolymerized fibrin and was not influenced by the presence of cross-linked alpha 2-plasmin inhibitor. In vivo lysis of implante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 60 publications
(106 reference statements)
0
29
0
Order By: Relevance
“…28, 38 -41). Quantitative studies of fibrinogen antigenic proteins in synovial fluid have correlated higher levels of these substances with higher inflammatory indices (38,39,42). A suspected role for fibrin in the pathogenesis of the disease is supported by many studies beginning with the early demonstration that chronic arthritis could be induced in rabbits by intra-articular fibrin injection (43).…”
Section: Discussionmentioning
confidence: 99%
“…28, 38 -41). Quantitative studies of fibrinogen antigenic proteins in synovial fluid have correlated higher levels of these substances with higher inflammatory indices (38,39,42). A suspected role for fibrin in the pathogenesis of the disease is supported by many studies beginning with the early demonstration that chronic arthritis could be induced in rabbits by intra-articular fibrin injection (43).…”
Section: Discussionmentioning
confidence: 99%
“…Extravascular cross-linked fibrin deposits have been detected in guinea pig carcinomas, in lymph nodes with Hodgkin's disease [51][52][53] and in rheumatoid synovial tissue [54,55]. Both plasma FXIII leaked out through the capillary wall and cellular FXIII derived from tumor associated and inflammatory macrophages [51,52,56] could contribute to the cross-linking process.…”
Section: Fxiiia-i Induced Cross-l Linking Reactions In the Fibrin Clomentioning
confidence: 99%
“…[13][14][15][16] Moreover, reduced levels of coagulation factors, with increased thrombin activity and thrombin-anti-thrombin complexes, have been found in RA synovial fluids. 17,18 More recently, it has been shown that intra-articular injection of either recombinant TF or TF/FVIIa complex in mice induces remarkable cellular infiltration of synovium, and cartilage and bone destruction, indicating direct proinflammatory properties of TF. 19,20 The function of the cytoplasmic domain of TF, which consists of only 21 residues in humans and 20 residues in mice, is primarily unknown.…”
mentioning
confidence: 99%